2006
DOI: 10.1523/jneurosci.5487-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Sensitive Afferents Inhibit Extensor but Not Flexor Motoneurons in Humans

Abstract: The role of group III and IV muscle afferents in controlling the output from human muscles is poorly understood. We investigated the effects of these afferents from homonymous or antagonist muscles on motoneuron pools innervating extensor and flexor muscles of the elbow. In study 1, subjects (n ϭ 8) performed brief maximal voluntary contractions (MVCs) of elbow extensors before and after a 2 min MVC of the extensors. During MVCs, electromyographic responses from triceps were evoked by stimulation of the cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 54 publications
9
163
4
Order By: Relevance
“…First, one would expect the inhibitory reflex feedback to affect a large number of motoneurons rather than just the target motoneuron. Second, it has been demonstrated that for the elbow flexors and extensors, group III-IV inhibition acts only on extensors and not on the flexors, thus meaning that this reflex inhibition is not universal (Martin et al 2006). In the present study, rotation has been observed in a variety of muscles including both extensors and flexors.…”
Section: Additional Factors Contributing To Rotationsupporting
confidence: 44%
“…First, one would expect the inhibitory reflex feedback to affect a large number of motoneurons rather than just the target motoneuron. Second, it has been demonstrated that for the elbow flexors and extensors, group III-IV inhibition acts only on extensors and not on the flexors, thus meaning that this reflex inhibition is not universal (Martin et al 2006). In the present study, rotation has been observed in a variety of muscles including both extensors and flexors.…”
Section: Additional Factors Contributing To Rotationsupporting
confidence: 44%
“…This is most likely due to the modified stimulation of motoneurons of elbow flexors (biceps) and extensors (triceps) by afferent nerve fibers [16,17]. A study by Butler et al [17] revealed that afferent signals from type III and type IV sensory fibres do not inhibit the activity of elbow flexor motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Group III/IV muscle afferent feedback associated with intramuscular metabolic perturbation has been suggested to have an inhibitory effect on the central nervous system (i.e., central fatigue), limiting the output of spinal motoneurons during exhaustive locomotor exercise (Amann et al 2013;Amann et al 2015;Hilty et al 2011;Sidhu et al 2014). Moreover, it has been suggested that decrease in the output from spinal motoneurons is attributed to the inhibitory effect of group III/IV muscle afferents on voluntary descending drive 'upstream' of the motor cortex (Taylor et al, 2006) and/or an afferent-mediated depression of excitability of the corticospinal tract (Hilty et al 2011, Martin et al 2006Martin et al 2008, Sidhu et al 2014. In the present study, MEP was significantly lower in IE 2nd than in IE 1st , while M max was similar in the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that reductions in the output from spinal motoneurons are attributed to the inhibitory effect of group III/IV muscle afferents on excitability of the corticospinal tract consisting of the motor cortex and spinal motoneurons (Hilty et al 2011;Martin et al 2006;Sidhu et al 2014). In this kind of situation, there is a possibility that activation of upstream regions of the motor cortex might be involved in the generation of a greater effort sense and consequently an increase in ventilation in order to maintain a required power output during IE (Amann et al 2013).…”
Section: Introductionmentioning
confidence: 99%